Optimalisasi Program SIJARES (Siap Jaga Remaja Sehat) dalam Meningkatkan Kesehatan dan Kesejahteraan Remaja Desa Dukong - Faldini, Mandala; Agustian, Nandi; Wulandari, Fitria (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Teenage problems are one that we must address comprehensively. Teenage problems are complex and diverse, ranging from academic, social, to emotional problems. The right approach will depend greatly on the root of the problem faced. Posyandu Remaja in the form of the SIJARES program is expected to be the right place for teenagers to facilitate teenagers in overcoming health and welfare problems in Dukong Village. The purpose of this activity is to create interesting health activities that are in accordance with the interests of Dukong Village teenagers with outbound activities and peer counseling for teenagers. Determining the right SIJARES activities is by creating questions before holding SIJARES activities. During the pre-test, Dukong Village teenagers did not yet fully understand the importance of reproductive health and had not been able to maximize their skills. Dukong Village teenagers were still afraid and embarrassed to talk about their reproductive problems. After the SIJARES activity, there was a very high increase with data showing 80% and above. The results of the activity showed the response of Dukong Village teenagers who had begun to protect and maintain their health, and were able to improve their welfare. This activity can invite teenagers from Dukong Village with 30 participants. This activity will continue to be carried out periodically with the formation of active cadres, and in collaboration with the Dukong Village health center.